Fall armyworm in Botswana: impacts, farmer management practices and implications for sustainable pest management. Issue 3 (2nd December 2021) - Makale, Fernadis; Mugambi, Idah; Kansiime, Monica K; Yuka, Irie; Abang, Mathew; Lechina, Bonolo S; Rampeba, Mosimanegape; Rwomushana, Ivan
Abstract: BACKGROUND: Since first reported in Botswana, fall armyworm (FAW) continues to be a threat to crop production. This study aimed to estimate impacts of FAW on yield and farmers' livelihoods in Botswana, and to obtain data that could be extrapolated to national level. Further, farmer knowledge of the pest, management practices and pesticide use for FAW management were assessed. RESULTS: In fact, 76% of the 220 respondents had seen FAW in their farms in the 2018/2019 cropping season, affecting almost the entire and about half of cultivated area for maize and sorghum, respectively. Thus, 51% of the respondents implemented FAW control measures, with chemical pesticides (27%) being the most common management against FAW. Only 33% of respondents in 2018/2019 were food self‐sufficient, as opposed to 80% in an ordinary year, with farmers who reported not to have been affected by FAW more likely to be insufficient with food (88%) compared to 60% of the farmers who reported FAW attack. Drought was ranked the major stress experienced by the famers (35%), and also showed significant yield reducing effects on maize yield with pest and diseases reported second most important. Pesticides (20%) and training on pest management (18%) were the top ranked needs by farmers interviewed. CONCLUSIONS: This study confirms the impact and threat of FAW to crop production in Botswana. Chemicals remain the go‐to control option by a majority of the farmers. Other low‐risk technologies exist and are proposed for adoption in the management of FAW. Of note is the acknowledgement that a single control strategy will not be effective against FAW and as such integrated pest management (IPM) on an area‐wide scale is needed to achieve best results. Mass awareness, training and demonstration will be required to achieve this. Abstract : Pesticides were the commonest control measures against fall armyworm (FAW). Drought was ranked the top stress with pesticides and training in pest management being the important needs prioritized by farmers. © 2021 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.